Gaya Kepemimpinan Kepala Sekolah terhadap Motivasi Prilaku Kerja Staff TU SMK Negeri 9 Sarolangun - Deri Emilia (J-MAS (Jurnal Manajemen dan Sains), 2021)
School Action Research is conducted collaboratively between researchers, observers, and subjects studied by Administration. The main objective in this study is to improve the results of pedagogic competence of administrative staff in arranging the administration of human resources schools is one of the fanctors that make the goal of an organization can be achieved, to see the leadership style to the motivation of administrative work in SMK Negeri 9 Sarolangun. The performance of administrative staff is closely related to the achievement of the objectives of an organization and cannot be separated from the human resources itself, especially in the influence of the leadership style of the democratic principal that becomes the motivation for administrative staff to achieve the goals of the school organization. The motivation of administrative staff work is closely related to the achievement of the objectives of a school organization, the influence of transformational leadership style on staff performance. Work motivation and leadership style to staff performance in the form of, quality of work, promptness, initiative, capaility, and communication